Răspuns :
[tex]\{6+2\times[4+6\times (3\times 10^2-299)]\}:13+1^{13}=\\\{6+2\times[4+6\times (3\times 100-299)]\}:13+1=\\\{6+2\times [4+6\times (300-299)]\}:13+1=\\{[6+2\times (4+6\times 1)]}:13+1=\\{[6+2\times (4+6)]}:13+1=\\(6+2\times 10):13+1=\\(6+20):13+1=\\26:13+1=\\2+1=\boxed{3}[/tex]
{6 + 2 · [4 + 6 · ( 3 · 10² - 299)]} : 13 + 1¹³ =
= {6 + 2 · [4 + 6 · (3 · 100 - 299)]} : 13 + 1 =
= {6 + 2 · [4 + 6 · (300 - 299)]} : 13 + 1 =
= [6 + 2 · (4 + 6 · 1)] : 13 + 1 =
= (6 + 2 · 10) : 13 + 1 =
= (6 + 20) : 13 + 1 = 26 : 13 + 1 = 2 + 1 = 3.
/rfd